Elites and inequality: A case study of plutocratic philanthropy in the UK - Luna Glucksberg; Louise Russell-Prywata (United Nations Research Institute for Social Development (UNRISD), 2020)
This paper investigates the role of elite philanthropy in the context of rising global inequality, asking whether large-scale philanthropic donations by elites are well placed to help tackle structural inequality. The challenges posed by such "plutocratic philanthropy" are explored through analysis of a network of the top 30 philanthropists in the United Kingdom and their connections to businesses and foundations, which shows their financial scale and connectivity. This new data is embedded into a review of the most recent social science literature on elites, which focuses on elite reproduction, how wealthy families perceive inequality, and how and why they engage in philanthropic activities. From this data, the paper develops an analysis of the current landscape of inequality, based on the work of British sociologist Mike Savage (2015), arguing that elite philanthropy as an ecosystem-made up of capital, people and institutions-is not well placed to systemically challenge inequalities, because the financial size of elites' philanthropy tends to be dwarfed by their business activities, and the social functions of philanthropy help maintain the advantaged positions of elites. The paper concludes with informed policy considerations on the role of elite philanthropy in light of the results of the analysis.
Keywords: 330; elite reproduction; foundations; network analysis; sustainable development; tax